Biomechanical engineering comparison of four leaflet repair techniques for mitral regurgitation using a novel 3-dimensional–printed left heart simulatorCentral MessagePerspective - Michael J. Paulsen, MD; Mateo Marin Cuartas, MD; Annabel Imbrie-Moore, MS; Hanjay Wang, MD; Robert Wilkerson, BS; Justin Farry, BSE; Yuanjia Zhu, MD; Michael Ma, MD; John W. MacArthur, MD; Y. Joseph Woo, MD (JTCVS Techniques)
Objective: Mitral valve repair is the gold standard treatment for degenerative mitral regurgitation; however, a multitude of repair techniques exist with little quantitative data comparing these approaches. Using a novel ex vivo model, we sought to evaluate biomechanical differences between repair techniques. Methods: Using porcine mitral valves mounted within a custom 3-dimensional–printed left heart simulator, we induced mitral regurgitation using an isolated P2 prolapse model by cutting primary chordae. Next, we repaired the valves in series using the edge-to-edge technique, neochordoplasty, nonresectional remodeling, and classic leaflet resection. Hemodynamic data and chordae forces were measured and analyzed using an incomplete counterbalanced repeated measures design with the healthy pre-prolapse valve as a control. Results: With the exception of the edge-to-edge technique, all repair methods effectively corrected mitral regurgitation, returning regurgitant fraction to baseline levels (baseline 11.9% ± 3.7%, edge-to-edge 22.5% ± 6.9%, nonresectional remodeling 12.3% ± 3.0%, neochordal 13.4% ± 4.8%, resection 14.7% ± 5.5%, P < 0.01). Forces on the primary chordae were minimized using the neochordal and nonresectional techniques whereas the edge-to-edge and resectional techniques resulted in significantly elevated primary forces. Secondary chordae forces also followed this pattern, with edge-to-edge repair generating significantly higher secondary forces and leaflet resection trending higher than the nonresectional and neochord repairs. Conclusions: Although multiple methods of degenerative mitral valve repair are used clinically, their biomechanical properties vary significantly. Nonresectional techniques, including leaflet remodeling and neochordal techniques, appear to result in lower chordal forces in this ex vivo technical engineering model.